Desenvolvimento de um método para gestão do ambiente de ensino aprendizagem em moléstias infecciosas com uma aplicação nos cursos de Medicina do Pará - CASTRO, Leny Silene de Freitas (Universidade Federal do Pará, 2017)
This study aimed at developing a method for the management of the learning and teaching environment in medicine schools around Pará state where nuisances and contagious diseases were the case scenario. Learning assessment was the central point of interest as it warrants the quality of education. To begin with, the academic contents on contagious diseases were selected from the syllabi in local medicine schools, followed by the identification of competencies and abilities in compliance with national standards. After contents, competencies and abilities had been identified, an assessment framework was created and used as a reference to construct question items that composed a test which was used for data collection. Next, this test was administered to 94 medicine sophomores, juniors, and seniors in medicine schools around the state. The test originally had 50 question items containing hard case – most of which were clinical cases. The Item Response Theory (IRT) and the Three- Parameter Logistic Model were used for the psychometric analysis of data. After item calibration, 10 items were deleted as they presented low or negative biserial correlation score (< 0.30). The test exhibited a Cronbach’s alpha of 0.96 which demonstrated the high degree of internal consistency. Among the forty remaining items, 9 were identified as milestones as they allowed the definition of a range of learner proficiency that discloses what contents, competencies and abilities had been consolidated by participants. The given range reflected the levels of student proficiency. From a pedagogical perspective, the results demonstrated the 400 to 600 level students had learned the contents, consolidated competencies, and developed the abilities expected for their year of undergraduate study. As a result of findings, a managerial method was proposed aiming at diagnosing and monitoring the learning and teaching environment. The method includes the following stages: organization of the lead group, creation of the assessment framework of reference, construction of the question items to compose the bank of items, and the creation of a final report. These components generate an assessment cycle. The information obtained in one assessment cycle can be used to guide problems identified in the development of learners.